Application of landuse approaches in controlling industrial wastewater discharge into rivers - Abdullah, Muhammad Faris (Malaysian Institute of Planners, 2004)
In Malaysia, water pollution is one of the major environmental problems facing the society at present, especially river water pollution. Despite their importance, especially as supply of water for consumption, rivers are continually being polluted by human. One of the main contributors to river water pollution in Malaysia is effluent (wastewater) discharge from industries.